Processo de reconhecimento do curso de graduação em Direito da UFPB - Campus Santa Rita: uma análise a partir do sistema nacional de avaliação da educação superior - Ribeiro, Ivana Leite (2022)
This dissertation aimed to analyze the last Evaluation Report of the Undergraduate Course in Law - Campus Santa Rita, from the Federal University of Paraíba (UFPB), based on the National System for the Evaluation of Higher Education (SINAES), made available by the Own Commission of Assessment (CPA) of the institution. Therefore, data collection was carried out through exploratory research through bibliographic and documentary research. For this purpose, the technique used to analyze the collected data was carried out using the SWOT tool (Strengths, Weaknesses, Opportunities, Threats). The objective was to provide subsidies for the improvement of the quality of the undergraduate course in Law at that campus, based on the identification of aspects related to strengths, weaknesses, opportunities and threats presented in the External Assessment Report carried out by INEP. In view of this, the research results showed that the institutional policies for teaching, research and extension were implemented in an excellent way, however, the faculty and infrastructure conditions are insufficient to meet the number of vacancies offered. It was also noted the need to invest in Information and Communication Technologies (ICTs) in the teaching-learning process, given its insufficiency for full compliance with the pedagogical project of the course, as well as the need for improvements in terms of scientific production in order to enable an improvement with a view to future regulatory processes that the course will undergo, in accordance with the precepts established by SINAES.